Suicide Risk Assessment in a Modern Asian Adolescent Community: A Cultural-relevant Perspective - Guo, Gideon Qinxian (Asian Journal of Interdisciplinary Research, 2023)
Suicide is a serious social and psychological issue that has a devastating socio-economic impact globally. However, it remains elusive as mental health professionals grapple to formulate effective assessment and intervention strategies. Particularly, there is a dearth of cultural-relevant suicide risk assessment scales as most instruments were developed in Western culture. Even with translation and linguistic equivalence, present suicide risk assessment scales do not encompass culturally salient and relevant psychological constructs. This study adopted a socio-cultural approach to develop a suicide risk assessment with sound psychometric properties and also to capture the cultural-specific symptomatology of suicide as well as depressive Asians.